Combinatorial optimization networks and matroids - Lawler Eugene (New York Dover, 2001)
This book is concerned with combinatorial optimization problems which can be formulated in terms of networks and algebraic structures known as matroids. Chapter 3 through 5 comprise the material in one-term courses on network flow theory currently offered
Keywords: Combinatorial optimization